Pengaruh Struktur Modal, Profitabilitas dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Tiara Putri; Ickhsanto Wahyudi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The research aims to determine the effect of capital structure, profitability and company size on company value in food and beverage sub-sector companies listed on the Indonesian Stock Exchange (BEI) from 2021 to 2023. In this research the independent variable used is capital structure. using Debt to Equity Ratio (DER), profitability using Return on Assets (ROA), and company size using natural logarithm (Ln) of total assets, and the dependent variable, namely company value using modified Tobin's Q. The population in this study was 95 food and beverage sub-sector companies. The sample was selected using a purposive sampling method with predetermined criteria so that 44 companies were collected over 3 years, resulting in 132 research samples. The data used is secondary data in the form of financial reports obtained from the website www.idx.co.id, measured using SPSS research tools. The results of this research reveal that capital structure has a significant negative effect on company value, profitability has an insignificant positive effect on company value, and company size has an insignificant negative effect on company value.